Collecting and Managing Tax Debt in Poland - Małgorzata Magdalena Hybka (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: The paper highlights the formation of tax debt, compares it among EU member states, examines certain factors contributing to its accumulation, and evaluates measures taken to manage tax debt collection.